Lipid profile in subclinical hypothyroidism: A biochemical study from tertiary care hospital - Mounika Guntaka; Babulreddy Hanmayyagari; Manne Rosaline; V Nagesh (Wolters Kluwer Medknow Publications, 2014)
Objective: To study lipid profile in patients of subclinical hypothyroidism and compare the same with matched controls. Materials and Methods: This single exposure observational study was conducted from June 2010 to March 2011 at our department of Biochemistry. Thirty patients with subclinical hypothyroidism were selected after careful exclusion; lipid profile was compared with matched controls. Statistical analysis was done with Student's t test. All values were expressed as mean ± SEM, where value of P ≤ 0.05 was considered statistically significant. Results: Between the two groups (group I - controls vs. group II - cases), the values were as follows: Mean serum total T 3 value was 115.03 ± 28.22 ng/dl vs. 107.13 ± 35.26 ng/dl (P = 0.3474); mean total T 4 was 7.0787 ± 1.6952 μg/dl vs. 6.8633 ± 1.3106 μg/dl (P = 0.532); mean TSH was 3.1730 ± 1.2772 μIU/ml vs. 9.7607 ± 4.1853 μIU/ml (P < 0.0001). Lipid profile pattern (group I vs. group II) was as follows: Mean total cholesterol (TC) 127.50 ± 7.18 mg/dl vs. 163.07 ± 41.32 mg/dl (P < 0.0001), mean triglycerides (TG) is 135.67 ± 13.84 mg/dl vs. 147.90 ± 66.27 mg/dl (P = 0.3231), low-density lipoprotein (LDL)-cholesterol is 61.17 ± 7.60 mg/dl vs. 99.83 ± 32.24 mg/dl (P < 0.0001), high-density lipoprotein (HDL)-cholesterol 39.13 ± 6.66 mg/dl vs. 35.27 ± 8.63 mg/dl (P = 0.0701), very low-density lipoprotein (VLDL) levels are 33.533 ± 14.375 mg/dl vs. 31.077 ± 14.202 mg/dl (P = 0.5235). Conclusion: Subclinical hypothyroidism is associated with increased serum total cholesterol and LDL-Cholesterol levels. Therefore, there is a potential association between Subclinical hypothyroidism and atherosclerosis.